Do probiotics, prebiotics and synbiotics affect adiponectin and leptin in adults? A systematic review and meta-analysis of clinical trials. Issue 5 (October 2019) - Rouhani, Mohammad Hossein; Hadi, Amir; Ghaedi, Ehsan; Salehi, Mina; Mahdavi, Atena; Mohammadi, Hamed
Summary: Background & aims: Human studies have reported controversial findings regarding the health promoting effects of probiotic, prebiotic and synbiotic on adiponectin and leptin levels. This systematic review and meta-analysis was conducted to understand the effect of probiotics, prebiotics or synbiotics on adiponectin and leptin levels in adults. Methods: Electronic searches were performed in PubMed, Scopus, Web of Science, Cochrane Library and Google scholar up to February 11, 2018 without any restriction. Controlled clinical trials, in any age of adults, which reported the effect of probiotic, prebiotic and synbiotic on serum level of adiponectin and leptin were included. As leptin and adiponectin were reported in different units across the studies, Hedges's adjusted g was used to calculate effect size. A random-effects model was used to pool calculated effect sizes. Results: Of 12 eligible studies, 10 publications focused on probiotics, and only 3 studies reported the effect of prebiotics ( n  = 2) or synbiotics ( n  = 1) on leptin and adiponectin. There were no significant changes in adiponectin (Hedges' g  = −0.04; 95% CI: −0.27, 0.19) and leptin (Hedges' g  = −0.30; 95% CI: −0.86, 0.26) in probiotic group compared with controls. Subgroup analyses ranged in heterogeneity from 0% to 93%, but no subgroup showed an effect of probiotics on adiponectin or leptin. Conclusion: There were limited studies regarding the effect of prebiotic and synbiotic on adiponectin and leptin. Although previous studies reported several health promoting effects of probiotics, we could not find any pooled effect on adiponectin and leptin.